TORAKOCHIRURGIAAcute oesophageal necrosis – a case report - Wójcik, Norbert; Wójcik, Janusz; Grodzki, Tomasz; Kubisa, Bartosz; Pieróg, Jarosław (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2010)
A case of a 59-year old woman with subtotal oesophageal necrosis is described. This state developed 9 days after earlier suture of an oesophageal wall rupture due to Boerhaave’s syndrome. She underwent three-field subtotal oesophagectomy with full recovery.